Technology and Entrepreneurship in Development: Bibliometric Analysis - Lucky Mahesa Yahya; I Wayan Adi Pratama; Ade Suhara (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study performs a bibliometric analysis to examine global research networks in entrepreneurship, emphasizing the changing collaborations among countries and regions. The study illustrates the pivotal importance of countries such as the United States, Germany, and the United Kingdom in research through the mapping of co-authorship networks from academic papers, while also acknowledging the growing impact of rising economies like China, India, and Brazil. The findings highlight the interdisciplinary character of entrepreneurship research, connecting it to economics, technology, and sustainable development. The study underscores the significance of entrepreneurial education, advocating for the incorporation of global viewpoints and technological innovations inside academic courses. The study provides useful insights into global research trends but acknowledges limitations, such as dependence on indexed databases and the omission of non-collaborative contributions. This analysis offers actionable insights for politicians, educators, and researchers aiming to promote innovation and entrepreneurship, highlighting the necessity of international cooperation to tackle global issues.